2012
DOI: 10.1002/ejoc.201201301
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Ar‐BINMOL Ligands by [1,2]‐Wittig Rearrangement to Probe Their Catalytic Activity in 1,2‐Addition Reactions of Aldehydes with Grignard Reagents

Abstract: We have demonstrated a highly diastereoselective synthesis of optically pure Ar‐BINMOL‐derived diols and their analogues. The present study demonstrates a unique cascade chirality transfer in a [1,2]‐Wittig rearrangement that leads to chiral diols with three stereogenic centers, which include a chiral sp3 center at the alcohol and C2‐axial chirality. Screening these ligands in the arylation of aromatic aldehydes with Grignard reagents shows that the naphthyl‐substituted BINMOL promotes the aryl transfer reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(14 citation statements)
references
References 105 publications
0
14
0
Order By: Relevance
“…Regretfully, only n-BuMgCl afforded slightly improved ee of 18% (entry 10). Then, solvents were observed, and THF and methyl tert-butyl ether (MTBE) obtained the highest enantioselectivity (28%) and MTBE obtained higher yield than THF (entries 10 and [16][17][18]. Then, the amount of L6 and n-BuMgCl was optimized, and the highest 60% of enantioselectivity was obtained (entries [16][17][18][19][20][21][22][23][24][25], indicating a possible chloride Grignard reagent complex A (Scheme 2) effectively catalyzing the asymmetric vinylation of aldehydes with the vinyl Grignard reagent.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regretfully, only n-BuMgCl afforded slightly improved ee of 18% (entry 10). Then, solvents were observed, and THF and methyl tert-butyl ether (MTBE) obtained the highest enantioselectivity (28%) and MTBE obtained higher yield than THF (entries 10 and [16][17][18]. Then, the amount of L6 and n-BuMgCl was optimized, and the highest 60% of enantioselectivity was obtained (entries [16][17][18][19][20][21][22][23][24][25], indicating a possible chloride Grignard reagent complex A (Scheme 2) effectively catalyzing the asymmetric vinylation of aldehydes with the vinyl Grignard reagent.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] Only recently successful strategies were developed in access to highly enantiopure secondary alcohols via catalytic asymmetric Grignard reactions. [11][12][13] The groups of Harada, [14][15][16] Xu, 17,18 and Yus 19,20 utilized superstoichiometric Ti (Oi-Pr) 4 to transmetallate RMgX (Br, Cl) to less reactive R-Ti (Oi-Pr) 3 , and then R-Ti (Oi-Pr) 3 highly enantioselectively delivered R group to aldehydes catalyzed by chiral diol-Ti (Oi-Pr) 2 complexes. Our group demonstrated that the additive bis([2-[N,N′-dimethylamino)]thyl) ether (BDMAEE) effectively deactivated the reactivity of Grignard reagents and then similarly transmetallated R functional group of RMgBr to R-Ti (Oi-Pr) 3 by using stoichiometric Ti (Oi-Pr) 4 .…”
Section: Introductionmentioning
confidence: 99%
“…The reaction shown in Scheme 18 could be considered a radical mechanism for the Truce-Smiles rearrangement when R 1 is an aryl ring; there are a limited number of examples from the literature wherein R 1 is an aryl ring. [56][57][58][59][60] These reported reactions are presumed to proceed via a [1,2]-Wittig rearrangement radical mechanism; however, a very similar reaction reported by Dudley and colleagues 58,61 is proposed to proceed via an anionic mechanism, and so the possibility that some reported [1,2]-Wittig rearrangements might correspond better with the definition of a Truce-Smiles rearrangements remains a possibility.…”
Section: Radical Mechanismsmentioning
confidence: 91%
“…The catalytic enantioselective 1,2-addition reaction of organometallic reagents to carbonyl compounds is one of the most efficient approaches to chiral alcohols. This transformation has been extensively studied with dialkylzinc [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ] and trialkylaluminium [ 18 , 19 , 20 ] reagents; more recently, excellent results with Grignard [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ] and organolithium [ 36 , 37 , 38 ] reagents have also been reported. The high reactivity and sometimes pyrophoric character of these premade, non-stabilized organometallic nucleophiles, however, restricts the implementation of these methodologies in industrial processes and large-scale reactions [ 39 ].…”
Section: Introductionmentioning
confidence: 99%